Trends And Research Gaps In Islamic Digital Business: A Bibliometric And Systematic Literature Review - Ihsan Mulia Siregar; Siti Ena Aisyah Simbolon; Siti Eni Aisyah Simbolon (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2026)
The rapid expansion of global digital transformation has positioned technology as a universal solution to economic challenges; however, it has also raised concerns regarding inequality, ethical erosion, and platform dominance. This study aims to examine Islamic digital business as an alternative paradigm that integrates technological innovation with Sharia-based values, and to identify research trends, gaps, and future research directions. This study employs a systematic literature review and bibliometric analysis, following the PRISMA framework. Data were collected from the Scopus database up to March 2026, resulting in 241 peer-reviewed journal articles after a rigorous screening process. VOSviewer was employed to analyze citation networks, keyword co-occurrence, and collaboration patterns. The findings indicate that research on Islamic digital business remains limited and fragmented, with a dominant focus on fintech, Islamic finance, and blockchain. In contrast, critical dimensions such as ethics, governance, and sustainability receive relatively limited attention. The study also reveals a geographical concentration of publications in specific regions, particularly in Muslim-majority countries. This study provides important implications by emphasizing the need to develop Islamic digital business as a holistic and value-driven framework that balances efficiency, ethics, and sustainability, while encouraging broader interdisciplinary and global research collaboration.